2020
DOI: 10.3390/app10196926
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a Nondestructive Method for Assessing the Humidity of Saline Brick Walls in Historical Buildings

Abstract: The paper presents the results of the verification of the neural method for assessing the humidity of saline brick walls. The method was previously developed by the authors and can be useful for the nondestructive assessment of the humidity of walls in historic buildings when destructive intervention during testing is not possible due to conservation restrictions. However, before being implemented in construction practice, this method requires validation by verification on other historic buildings, which to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Article [11] presents the results of the verification of a method of assessing the moisture content of saline brick walls based on non-destructive measurements and artificial intelligence. The method was formerly developed and can be suitable for the non-destructive identification of the moisture content of walls in historic buildings when destructive interference during the research is not possible because of the conservation limitations.…”
Section: Analysis Of the Results Of Non-destructive Testing Including...mentioning
confidence: 99%
“…Article [11] presents the results of the verification of a method of assessing the moisture content of saline brick walls based on non-destructive measurements and artificial intelligence. The method was formerly developed and can be suitable for the non-destructive identification of the moisture content of walls in historic buildings when destructive interference during the research is not possible because of the conservation limitations.…”
Section: Analysis Of the Results Of Non-destructive Testing Including...mentioning
confidence: 99%
“…The test that was carried out showed that it is possible to reliably identify the moisture content of saline brick walls using the proposed approach without the necessity of interference in the wall structure. Next, the method proposed in [9] was successfully validated by investigating the moisture content in two historic buildings other than those used for the learning and testing of the artificial neural networks [10]. Orr et al [11] evaluated the performance of microwave sensors and radar for monitoring the moisture movement in the masonry walls subjected to wind-driven rain.…”
Section: Introductionmentioning
confidence: 99%